Frontiers in the Actin Cytoskeleton - Rivero, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of IJMS covers a broad range of cutting-edge aspects related to the organization, function, and role in disease of the actin cytoskeleton. This cellular structure is of fundamental importance for the homeostasis of every eukaryotic cell, from the simplest unicellular organism to the most complex animal cell. The actin cytoskeleton contributes to developing and maintaining cell shape and tissue integrity and is crucial for cell migration, movement of organelles, vesicle trafficking, and the completion of cell division. Elaborate structures like the sarcomere, the inner ear cell stereocilia, and the brush border microvilli are built on actin filament scaffolds. Dozens of actin-binding proteins orchestrate the dynamic remodeling of the actin cytoskeleton and integrate it with microtubules and intermediate filaments and with the cell signaling machinery. Playing such fundamental roles in a plethora of cellular processes, it comes as no surprise that defects in actin and associated proteins have been found to be implicated in pathological conditions as diverse as myopathies and neurodegenerative diseases. This Special Issue gathers 15 contributions highlighting the impressive advances made in recent years in this exciting field.